Migrating a professional field of study in a multi-institutional partnership: facilitators' experience in the competence-based curriculum development process - Proscovia Namubiru Ssentamu; Betty Akullu Ezati; Ronald Bisaso; Elias Pekkola; Seppo Hölttä (Universidad de Deusto, 2014)
With the urge to Africanise the curriculum following colonisation, many African countries are still wary of the educational initiatives from the developed countries. However, with the clear curriculum design and development guidelines provided by various national Quality Assurance bodies, African countries need not fear migrating curricula from developed countries. Drawing from the workshop experiences, authors of this paper illustrate the steps involved in migrating, contextualising and adapting a professional field of study in a multi-institutional partnership, with particular focus on the competence-based curriculum design and development process. The process of migrating higher education (HE) Administration, Leadership and Management curriculum taught at the University of Tampere (Finland) to a Postgraduate Diploma in Higher Education Leadership and Management (PGDHELM) curriculum at Uganda Management Institute (UMI) in partnership with the Makerere University and the University of Helsinki involved undertaking a needs assessment, training of trainers and adapting the programme to the UMI context. The training of trainers provided opportunity for the trainees to reflect and generate information on the status of HE leadership and management in Uganda. The curriculum was institutionalised by aligning it to the vision, mission and profile of UMI in the context of the existing internal and external Quality Assurance frameworks. This paper underscores the importance of involving stakeholders, taking into account national and institutional requirements in all the steps when migrating an academic curriculum.